Gene-activated matrix harboring a miR20a-expressing plasmid promotes rat cranial bone augmentation. Issue 2 (13th March 2021) - Shido, Rena; Sumita, Yoshinori; Hara, Masahito; Iwatake, Mayumi; Narahara, Shun; Umebayashi, Mayumi; Miura, Kei-ichiro; Kodama, Yukinobu; Asahina, Izumi
Abstract: Gene-activated matrix (GAM) has a potential usefulness in bone engineering as an alternate strategy for the lasting release of osteogenic proteins but efficient methods to generate non-viral GAM remain to be established. In this study, we investigated whether an atelocollagen-based GAM containing naked-plasmid ( p ) DNAs encoding microRNA (miR) 20a, which may promote osteogenesis in vivo via multiple pathways associated with the osteogenic differentiation of mesenchymal stem/progenitor cells (MSCs), facilitates rat cranial bone augmentation. First, we confirmed the osteoblastic differentiation functions of generated p DNA encoding miR20a ( p miR20a) in vitro, and its transfection regulated the expression of several of target genes, such as Bambi1 and PPARγ, in rat bone marrow MSCs and induced the increased expression of BMP4. Then, when GAMs fabricated by mixing 100 μl of 2% bovine atelocollagen, 20 mg β-TCP granules and 0.5 mg (3.3 μg/μl) AcGFP plasmid-vectors encoding miR20a were transplanted to rat cranial bone surface, the promoted vertical bone augmentation was clearly recognized up to 8 weeks after transplantation, as were upregulation of VEGFs and BMP4 expressions at the early stages of transplantation. Thus, GAM-based miR delivery may provide an alternative non-viral approach by improving transgene efficacy via a small sequence that can regulate the multiple pathways.